Linking the Rights of Peasants to the Right to Food in the United Nations. (June 2014) - Edelman, Marc
This article analyzes two convergent processes: (1) the increasing specification of the right to food in international law; and (2) the efforts of transnational agrarian social movements, notably Vía Campesina, to have the United Nations adopt an instrument on the rights of peasants. Because one-seventh of humanity suffers from hunger and because the right to food has wide support among UN member states and is essential for the enjoyment of all other rights, it has become a magnet for diverse kinds of rights claims. Vía Campesina has elaborated a draft instrument that has received growing attention in the UN Human Rights Council. Several of the claimed rights, however, are contentious and have generated opposition from powerful UN member states.